Landholding and Agriculture in Late Ramesside Theban Documents - Antoine, Jean-Christophe (Zeitschrift für ägyptische Sprache und Altertumskunde, 2015)
Agriculture and land management are recurring topics in the Late Ramesside Letters. Eight of them completed with P Turin Cat 2084 and P Berlin 8523 illustrate the agricultural methods used for farming cereals, fruits and vegetables in the late New Kingdom. They show that although necessitating extra work, artificial irrigation was frequent on small parcels located on ı͗db , nḫb or Ꜥ m Ꜥ m types of land. The two traditional categories of landholding, institutional and private, are distinguished, but their management overlapped when the landholder was involved in both systems. People farming the land pertained to the Necropolis workers, the memorial temple of Ramesses III, the Necropolis scribes household, or were sharecropper peasants living in countryside villages. Landholders behave as managerial landlords while technical terms specify the juridical frame within which subaltern people farmed the land. The land was assigned ( swḏ ) to them and they were responsible for fulfilling the “mission of the fields” ( sḥn Ꜣ ḥt ) at the risk of having their right to till the land withdrawn ( nḥm ) if they failed.